1994
DOI: 10.1346/ccmn.1994.0420203
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Surface Modification by an Organosilane on the Electrochemical Properties of Kaolinite

Abstract: Abstract--The electrochemical properties of kaolinite before and after modification with chlorodimethyloctadecylsilane have been studied by electrophoretic mobility, surface charge titration, and extrapolated yield stress measurements as a function of pH and ionic strength. A heteropolar model of kaolinite, which views the particles as having a pH-independent permanent negative charge on the basal planes and a pHdependent charge on the edges, has been used to model the data. The zeta potential and surface char… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0
2

Year Published

1996
1996
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(46 citation statements)
references
References 31 publications
1
43
0
2
Order By: Relevance
“…-~ 4.8 at the lowest ionic strength, but the disagreement between the model predictions and experimental aH data was significant. As with Braggs et al (1994), a short equilibration time in the experiments of Schindler et al (1987) is a possible explanation of a lower p.z.n.p.c. Zhou and Gunter (1992) did not report an equilibration time but their titration data indicate p.z.n.p.c.…”
Section: Points Of Zero Chargementioning
confidence: 81%
See 1 more Smart Citation
“…-~ 4.8 at the lowest ionic strength, but the disagreement between the model predictions and experimental aH data was significant. As with Braggs et al (1994), a short equilibration time in the experiments of Schindler et al (1987) is a possible explanation of a lower p.z.n.p.c. Zhou and Gunter (1992) did not report an equilibration time but their titration data indicate p.z.n.p.c.…”
Section: Points Of Zero Chargementioning
confidence: 81%
“…The corresponding ranges for qo were -0.2 to +5.2 and 2.7 to 8.1 mmolc kg -~ (data not shown), decreasing with increasing -log[H+]. In general, qLi and qcl both decreased with increasing equilibration time for a given -log[H+], although this trend was more marked for qLi ' Braggs et al (1994) found p.z.n.p.c. --~ 3 for a Georgia kaolinite, far below the values reported in this study.…”
Section: Points Of Zero Chargementioning
confidence: 87%
“…Thus, the exchange sites were energeti cally homogeneous in the Oxisol. The main com ponents capable of cation exchange at the pH of the experiment (pH ϭ 4.7) were organic matter and kaolinite (ZPCs Ͻ 3 and 3 to 5, respectively; Braggs et al, 1994;Ferris and Jepson 1975;Sparks, 1995). Both materials have external cation ex APPEL, RHUE, MA, AND REVE SOIL SCIENCE change sites, which may exhibit constant affinities for K as exchangeable K content varies.…”
Section: Differential Heats Of Adsorptionmentioning
confidence: 99%
“…The objective of the acid pre-treatment is to remove octahedral cations, each of which leaves behind two additional Si-OH groups (RausellColom and Serratosa, 1987). Kaolinite, with edge-OH groups estimated at --10%, was examined also by direct reaction with silane in solvent (Braggs et aL, 1994). Sepiolite, with a comparatively larger -OH content, was examined for direct grafting either with ~'Present address: Novellus Systems, Inc., 4000 N. First Street, M/S 81A, San Jose, California 95134, USA.…”
Section: Introductionmentioning
confidence: 99%